2007
DOI: 10.3130/jaabe.6.371
|View full text |Cite
|
Sign up to set email alerts
|

Energy Savings Potential of the Summer Time Concept in Different Regions of JapanFrom the Perspective of Household Lighting

Abstract: Summer Time is a convention in which clocks are uniformly set one hour or more ahead of standard time to provide more daylight in the evenings during late spring, summer, and early fall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…A similar methodology is employed in two recent studies that take place in Japan, where DST is continually debated but not currently practiced. Fong et al (2007) use a simulation model to investigate the effects of DST on household lighting, and they find a reduction in electricity consumption that differs by region. 7 Shimoda et al (2007) conduct a similar exercise, with the added consideration of DST's effect on residential cooling.…”
Section: Existing Evidencementioning
confidence: 99%
“…A similar methodology is employed in two recent studies that take place in Japan, where DST is continually debated but not currently practiced. Fong et al (2007) use a simulation model to investigate the effects of DST on household lighting, and they find a reduction in electricity consumption that differs by region. 7 Shimoda et al (2007) conduct a similar exercise, with the added consideration of DST's effect on residential cooling.…”
Section: Existing Evidencementioning
confidence: 99%
“…Desde una perspectiva diferente, Rock (1997) se acoge a un modelo de simulaci贸n para predecir el uso de energ铆a en una residencia representativa de los Estados Unidos y descubre que el consumo de electricidad aumenta ligeramente cuando se emplea el DST. De modo similar, Fong et al (2007) simulan una variedad de escenarios de tiempo de ahorro de luz diurna para distintas regiones en Jap贸n y concluyen que un DST por doble partida (es decir, + 2 horas.) constituir铆a el marco 贸ptimo para el consumo energ茅tico en los hogares.…”
Section: La Evidencia Existenteunclassified
“…Recent investigations include those by Brock (1997), the California Energy Commission (CEC, 2001), University of California Energy Institute (UCEI, 2007), Fong et al (2007), Shimoda et al (2007), Kotchen andGrant (2008), Beltzer et al (2008), and Momani et al (2009). Brock used a simulation analysis to determine the impact of DST on the energy use of a typical single family home throughout the US (Brock, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…The data analysis indicated that the extension of DST actually increased both electricity energy use and peak demand. Fong et al (2007) used a simulation analysis to assess the impact of DST on the residential sector in Japan. They found that DST reduces household lighting energy use but the magnitude of the reduction depends on the location.…”
Section: Introductionmentioning
confidence: 99%